Agronomic performance and genetic progress of selected historical soybean varieties in the southern USA. Issue 1 (23rd December 2014) - Rogers, Justin; Chen, Pengyin; Shi, Ainong; Zhang, Bo; Scaboo, Andrew; Smith, S. Faye; Zeng, Ailan; Singh, R.
Abstract This study was conducted to compare recently developed and historical soybean varieties and evaluate genetic gain in yield and other agronomic traits in the southern USA. A total of 45 southern varieties from public breeding programs, which were released from 1928 to 2008, were used in this study. Three experiments were conducted in 2007 and 2008 at Keiser, Stuttgart, and Marianna in Arkansas (USA). Varieties with maturity groups (MG) late IV to early V had a yield gain of 21.7 kg/ha/yr from the 1950s to the 2000s, mid to late MG V had a yield gain of 16.4 kg/ha/yr from the 1940s to the 2000s, and MG VIs had a yield gain of 12.4 kg/ha/yr from the 1920s to the 2000s. Yield increased linearly for all combined experiments by 16.8 kg/ha/yr. Plant height remained steady over time for most experiments. No significant changes were observed in maturity. Lodging scores decreased, protein concentration decreased, and oil concentration increased linearly over time for all combined experiments. Hutcheson, Narrow, R97‐1634, and Young were recommended as parent lines in future soybean breeding efforts.